2008
DOI: 10.1159/000191213
|View full text |Cite
|
Sign up to set email alerts
|

Low Levels of Corticotropin-Releasing Hormone during Early Pregnancy Are Associated with Precocious Maturation of the Human Fetus

Abstract: Elevation in placental corticotropin-releasing hormone (pCRH) during the last trimester of pregnancy has been associated with an increased risk for preterm delivery. Less is known about the consequences for the human fetus exposed to high levels of pCRH early in pregnancy. pCRH levels were measured in 138 pregnant women at least once at 15, 20 and 25 weeks of gestation. At 25 weeks of gestation, fetal heart rate (FHR) responses to a startling vibroacoustic stimulus (VAS) were recorded as an index of maturity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 108 publications
2
34
0
1
Order By: Relevance
“…To evaluate programming influences on the fetus, we assessed the consequences of gestational stress during the early second trimester on fetal behavior in the early third trimester. We found that low CRH at 15 gestational weeks, but not later, predicted a more mature fetal heart rate pattern at 25 gestational weeks (Class et al, 2008). This is evidence that endocrine stress exerted influence, on the developing nervous system and that these effects may influence directly or indirectly, birth outcome Sandman et al, 2011b).…”
Section: Fetal Behaviorsupporting
confidence: 49%
“…To evaluate programming influences on the fetus, we assessed the consequences of gestational stress during the early second trimester on fetal behavior in the early third trimester. We found that low CRH at 15 gestational weeks, but not later, predicted a more mature fetal heart rate pattern at 25 gestational weeks (Class et al, 2008). This is evidence that endocrine stress exerted influence, on the developing nervous system and that these effects may influence directly or indirectly, birth outcome Sandman et al, 2011b).…”
Section: Fetal Behaviorsupporting
confidence: 49%
“…To evaluate programming influences on the fetus, we assessed the consequences of gestational stress during the early second trimester on fetal behavior in the early third trimester. We found that low pCRH at 15 gestational weeks, but not later, predicted a more mature FHR pattern at 25 gestational weeks [43,44]. This is evidence of gestational stress exerting programming influences on the developing nervous system that is independent of postnatal experiences.…”
Section: Gestational Stress Influences Human Fetal Behaviormentioning
confidence: 72%
“…83 Successful lactation, therefore, requires mature infant suck-swallow patterns; maternal depression may affect this oromotor development. Exposure to elevated CRH during pregnancy has been linked with differences in neurologic maturation 84 and neuromuscular development. 85 At birth, neonates born to depressed mothers exhibit different suckling responses than those born to euthymic mothers.…”
Section: Infant Developmentmentioning
confidence: 99%